The two phases of core formation – orbital evolution in the centres of ellipticals with supermassive black hole binaries. Issue 3 (2nd October 2021) - Frigo, M; Naab, T; Rantala, A; Johansson, P H; Neureiter, B; Thomas, J; Rizzuto, F
ABSTRACT: The flat stellar density cores of massive elliptical galaxies form rapidly due to sinking supermassive black holes (SMBHs) in gas-poor galaxy mergers. After the SMBHs form a bound binary, gravitational slingshot interactions with nearby stars drive the core regions towards a tangentially biased stellar velocity distribution. We use collisionless galaxy merger simulations with accurate collisional orbit integration around the central SMBHs to demonstrate that the removal of stars from the centre by slingshot kicks accounts for the entire change in velocity anisotropy. The rate of strong (unbinding) kicks is constant over several hundred Myr at 3 M_ yr^-1 for our most massive SMBH binary ( M BH = 1.7 × 10 10 M⊙ ). Using a frequency-based orbit classification scheme (box, x-tube, z-tube, rosette), we demonstrate that slingshot kicks mostly affect box orbits with small pericentre distances, leading to a velocity anisotropy of β ≲ −0.6 within several hundred Myr as observed in massive ellipticals with large cores. We show how different SMBH masses affect the orbital structure of the merger remnants and present a kinematic tomography connecting orbit families to integral field kinematic features. Our direct orbit classification agrees remarkably well with a modern triaxial Schwarzschild analysis applied to simulated mock kinematic maps.